Polymer biquinolyl-containing complexes of Pd(ii) as efficient catalysts for cyanation of aryl and vinyl halides with K4Fe(CN)6. (15th November 2016) - Nikitin, Oleg M.; Polyakova, Olga V.; Sazonov, Petr K.; Yakimansky, Alexander V.; Goikhman, Mikhail Ya.; Podeshvo, Irina V.; Magdesieva, Tatiana V.
Abstract : Stereo- and chemoselective cyanation of compounds containing Csp 2 –Br bonds catalyzed by Pd–polymer complexes is reported. Abstract : A catalytic system for cyanation of aryl and vinyl halides with K4 Fe(CN)6 based on a structurally tunable and nontoxic polymer backbone of polyamic type with biquinolyl fragments in the polymer chain capable of coordination to Pd II ions is developed. The catalyst is eligible for thermal and microwave activation; in the latter case the reaction time is dramatically decreased. Cyanation of vinyl bromides occurs stereoselectively, and the configuration of the starting alkene is retained; even for Z -isomers the impact of configuration inversion is less than 5%. The polymer-based Pd catalyst is applicable for one-pot multi-step synthesis of the precursors of mesogenic structures of biphenyl type. Consecutive cross-coupling and cyanation reactions can be performed in the presence of the same portion of catalyst, in the same solvent, without isolation of intermediate products.